System Assessment of WUSN Using NB-IoT UAV-Aided Networks in Potato Crops - Castellanos, German; Deruyck, Margot; Martens, Luc; Joseph, Wout (IEEE, 2020)
Unmanned Aerial Vehicles (UAV) are part of precision agriculture; also, their impact on fast deployable wireless communication is offering new solutions and systems never envisioned before such as collecting information from underground sensors by using low power Internet of Things (IoT) technologies. In this paper, we propose a (Narrow Band IoT) NB-IoT system for collecting underground soil parameters in potato crops using a UAV-aided network. To this end, a simulation tool implementing a gateway mounted on a UAV using NB-IoT based access network and LTE based backhaul network is developed. This tool evaluates the performance of a realistic scenario in a potato field near Bogota, Colombia, accounting for real size packets in a complete IoT application. While computing the wireless link quality, it allocates access and backhaul resources simultaneously based on the technologies used. We compare the performance of wireless underground sensors buried in dry and wet soils at four different depths. Results show that a single drone with 50 seconds of flight time could satisfy more than 2000 sensors deployed in a 20 hectares field, depending on the buried depth and soil characteristics. We found that an optimal flight altitude is located between 60 m and 80 m for buried sensors. Moreover, we establish that the water content reduces the maximum reachable buried depth from 70 cm in dry soils, down to 30 cm in wet ones. Besides, we found that in the proposed scenario, sensors' battery life could last up to 82 months for above ground sensors and 77 months for the deepest buried ones. Finally, we discuss the influence of the sensor's density and buried depth, the flight service time and altitude in power-constrained conditions and we propose optimal configuration to improve system performance.

Los vehículos aéreos no tripulados (UAV) forman parte de la agricultura de precisión; además, su impacto en la comunicación inalámbrica de rápido despliegue está ofreciendo nuevas soluciones y sistemas nunca antes previstos, como la recogida de información de sensores subterráneos mediante el uso de tecnologías del Internet de las cosas (IoT) de baja potencia. En este trabajo, proponemos un sistema (Narrow Band IoT) NB-IoT para la recogida de parámetros del suelo subterráneo en cultivos de patata utilizando una red asistida por UAV. Para ello, se desarrolla una herramienta de simulación que implementa una pasarela montada en un UAV utilizando una red de acceso basada en NB-IoT y una red de retorno basada en LTE. Esta herramienta evalúa el rendimiento de un escenario realista en un campo de patatas cerca de Bogotá, Colombia, teniendo en cuenta paquetes de tamaño real en una aplicación completa de IoT. Mientras computa la calidad del enlace inalámbrico, asigna los recursos de acceso y backhaul simultáneamente basándose en las tecnologías utilizadas. Comparamos el rendimiento de los sensores inalámbricos subterráneos enterrados en suelos secos y húmedos a cuatro profundidades diferentes. Los resultados muestran que un solo dron con 50 segundos de vuelo podría satisfacer a más de 2000 sensores desplegados en un campo de 20 hectáreas, dependiendo de la profundidad enterrada y de las características del suelo. Encontramos que una altitud de vuelo óptima se sitúa entre 60 m y 80 m para los sensores enterrados. Además, establecemos que el contenido de agua reduce la profundidad máxima alcanzable enterrada de 70 cm en suelos secos, hasta 30 cm en los húmedos. Además, descubrimos que en el escenario propuesto, la vida de la batería de los sensores podría durar hasta 82 meses para los sensores en superficie y 77 meses para los más enterrados. Por último, analizamos la influencia de la densidad del sensor y la profundidad de enterrado, el tiempo de servicio de vuelo y la altitud en condiciones de energía limitada y proponemos una configuración óptima para mejorar el rendimiento del sistema.
Keywords: Internet de las cosas; Internet of things; Redes de sensores inalámbricos; Wireless sensor networks; Precision agriculture; NB-IoT; Unmanned aerial vehicles; Wireless underground sensor networks